FORM OF DISTRIBUTION OF SCHOOL OPERATIONAL ASSISTANCE FUNDS IN MAS ISLAMIYAH SUNGGAL - Aburrasyid, Aburrasyid; Panggabean, Hadi Saputra; Waruwu, Ahmad Aswan (Proceeding International Seminar of Islamic Studies, 2023)
The school operational assistance fund (BOS) program arose due to the compensation program for reducing fuel subsidies, The distribution of the BOS program has fought a significant war in accelerating the achievement of the 9-year compulsory education program and then developed up to 15 years. Therefore, starting in 2009 the government has changed the objectives, approach and orientation of the BOS program, from expanding access to improving quality. There are many reports about the nation's children who have dropped out of school because of the absence of fees. This raises many questions why they dropped out of school even though the government has provided school operational assistance funds, this fund is allocated to underprivileged people, this is what indicates that this school operational assistance fund has been done a lot by schools that receive BOS funds that are distributed to underprivileged students. In addition to the news, the author here makes preliminary observations where the author gets things that are stuck about the BOS fund itself in the author's village. There is one school that in the view of the author of the school is far from being called perfection. The school does not have a library.